Viral metagenomics reveals diverse viruses in the fecal samples of children with acute respiratory infection - Pan Xu; Chunduo Pan; Minli Yuan; Ying Zhu; Shanjie Wei; Hongyan Lu; Wen Zhang (Frontiers in Microbiology)
IntroductionChanges in the gut microbiome have been associated with the development of acute respiratory infection (ARI). However, due to methodological limitations, our knowledge of the gut virome in patients with ARIs remains limited.MethodsIn this study, fecal samples from children with ARI were investigated using viral metagenomics.ResultsThe fecal virome was analyzed, and several suspected disease-causing viruses were identified. The five viral families with the highest abundance of sequence reads were Podoviridae, Virgaviridae, Siphoviridae, Microviridae, and Myoviridae. Additionally, human adenovirus, human bocavirus, human astrovirus, norovirus, and human rhinovirus were detected. The genome sequences of these viruses were respectively described, and phylogenetic trees were constructed using the gene sequences of the viruses.DiscussionWe characterized the composition of gut virome in children with acute respiratory infections. However, further research is required to elucidate the relationship between acute respiratory infection and gut viruses.